If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 3(x + -7) + 10 Reorder the terms: 7 = 3(-7 + x) + 10 7 = (-7 * 3 + x * 3) + 10 7 = (-21 + 3x) + 10 Reorder the terms: 7 = -21 + 10 + 3x Combine like terms: -21 + 10 = -11 7 = -11 + 3x Solving 7 = -11 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + -3x = -11 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + -3x = -11 + 0 7 + -3x = -11 Add '-7' to each side of the equation. 7 + -7 + -3x = -11 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = -11 + -7 -3x = -11 + -7 Combine like terms: -11 + -7 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| 8x=16(x-36) | | x=-5+4 | | 3x+15=6x+7 | | 3(2-a)=8-a | | 3x-8=5(2x-3) | | 147-4x=23x+21 | | 5x=(6x-3) | | 5(2x-3)+6=43-3x | | 8+12x=15x-19 | | 2c+5=3c+7 | | 67-5x=9x+7 | | 3a-11=4 | | 60-x=2(x-36) | | 2x+6=-3 | | 104-x=2(x-29) | | 20x-9x-20=0 | | 3x+139=12x-14 | | x-9x-20=0 | | 4x-2=11x-43 | | 49-6x=12x+15 | | 5m(2m-7)=-5 | | -8x-y=-8 | | x^3-8x^2+15x+12=0 | | 2x^2-11x-24=0 | | 2(x+3)-3=8-2x | | -21-9x=-32-9x | | 114-3x=24x+18 | | 8-7x=93-42x | | 7,000,000a=10 | | -8b-10=-7-6b | | -2(7w-5)+4w=2(w+2) | | 48x^2=0 |